Education and armed conflict: consequences on the population of children and adolescents in Colombia - Gómez Díaz, Jaime Eduardo; Quiroz Guzmán, Fredy; Ortegón Ávila , Sandra; Rojas Torre, Yosimar (Revista Colombiana de Ciencias Sociales, 2022)
Throughout history, the right to education has been a determining and unquestionably necessary factor for the improvement of people; however, as a socio-political process, it has not been free of adversities. In this sense, for more than six decades, Colombia has lived in the context of an internal armed conflict.